Understanding the transport networks complex between South Asia, Southeast Asia and China during the late Neolithic and Bronze Age. (February 2023) - Ma, Minmin; Lu, Yongxiu; Dong, Guanghui; Ren, Lele; Min, Rui; Kang, Lihong; Zhu, Zhonghua; Li, Xiaorui; Li, Bo; Yang, Zhijian; Cili, Nongbu; Liu, Ruiliang; et al.
The emergence and intensification of transcontinental exchange during both the Late Neolithic and Bronze Age profoundly influenced the social history of Eurasia. While scholars have intensively discussed east-west long-distance communication along the proto-Silk Road, the north-south transport networks that connected China to South and Southeast Asia during the Late Neolithic and Bronze Age have attracted much less attention in the scholarly literature based on archeological science data. In this paper, we find new radiocarbon dates from 11 Neolithic and Bronze Age sites in northwestern and central Yunnan in Southwest China, a key entrance into South and Southeast Asia from China. Combined with previously published archeological records and radiocarbon dates, we attempt to disentangle and understand the timing and routes of the networks linking China to South and Southeast Asia during the Late Neolithic and Bronze Age. We propose three north-south land routes that played essential roles in the cultural exchanges in addition to the proto-Silk Road and maritime routes. This includes the trans-Himalayan routes, trans-Hengduan Mountain routes, and the trans-Yunnan–Guizhou Plateau routes. The north-south exchange between China and South and Southeast Asia probably emerged in the fifth millennium BP (before the present) mainly through a low-frequency trans-Yunnan–Guizhou Plateau and trans-Himalayan routes. The exchange frequency significantly increased after the fourth millennium BP, with the synchronous development of the three primary north-south passageways. Trans-Hengduan routes might have been the most crucial artery connecting China and South and Southeast Asia during 3000–2200 BP, but more archeological records are needed to understand the detailed evolution of these transport networks.